2 - African Media, Information Providers¹ and Emigrants as Collaborative Nodes in Virtual Social Networks - Anthony A. Olorunnisola, (African Sociological Review, 2000)
This paper proposes that the Internet offers African media and informa tion providers the opportunity to elevate their current engagement to that of "content providers" to African emigrants in the diaspora. The paper finds evidence in the intercultural adjustment and social networks litera ture to support the feasibility of such an interaction. Further, a composite profile of African emigrants in the diaspora allows the discussion of ways in which they represent 'virtual' communities whose on- and off-line dis courses can be enriched by African content providers 'participation. The proposed engagement finds African content providers and emigrants interacting as active nodes in computer-mediated social networks. Among other possibilities, the paper views the evolvement as one that should enable African media organizations to widen their domestic margin of political freedom. The paper's propositions have both policy and research implications.